Supportive therapy for schizophrenia - Buckley, Lucy A (Cochrane Database Syst Rev, 2015)
BACKGROUND: Supportive therapy is often used in everyday clinical care and in evaluative studies of other treatments. OBJECTIVES: To review the effects of supportive therapy compared with standard care, or other treatments in addition to standard care for people with schizophrenia. SEARCH METHODS: For this update, we searched the Cochrane Schizophrenia Group's register of trials (November 2012). SELECTION CRITERIA: All randomised trials involving people with schizophrenia and comparing supportive therapy with any other treatment or standard care. DATA COLLECTION AND ANALYSIS: We reliably selected studies, quality rated these and extracted data. For dichotomous data, we estimated the risk ratio (RR) using a fixed‐effect model with 95% confidence intervals (CIs). Where possible, we undertook intention‐to‐treat analyses. For continuous data, we estimated the mean difference (MD) fixed‐effect with 95% CIs. We estimated heterogeneity (I(2) technique) and publication bias. We used GRADE to rate quality of evidence. MAIN RESULTS: Four new trials were added after the 2012 search. The review now includes 24 relevant studies, with 2126 participants. Overall, the evidence was very low quality. We found no significant differences in the primary outcomes of relapse, hospitalisation and general functioning between supportive therapy and standard care. There were, however, significant differences favouring other psychological or psychosocial treatments over supportive therapy. These included hospitalisation rates (4 RCTs, n = 306, RR 1.82 CI 1.11 to 2.99, very low quality of evidence), clinical improvement in mental state (3 RCTs, n = 194, RR 1.27 CI 1.04 to 1.54, very low quality of evidence) and satisfaction of treatment for the recipient of care (1 RCT, n = 45, RR 3.19 CI 1.01 to 10.7, very low quality of evidence). For this comparison, we found no evidence of significant differences for rate of relapse, leaving the study early and quality of life. When we compared supportive therapy to cognitive behavioural therapy CBT), we again found no significant differences in primary outcomes. There were very limited data to compare supportive therapy with family therapy and psychoeducation, and no studies provided data regarding clinically important change in general functioning, one of our primary outcomes of interest. AUTHORS' CONCLUSIONS: There are insufficient data to identify a difference in outcome between supportive therapy and standard care. There are several outcomes, including hospitalisation and general mental state, indicating advantages for other psychological therapies over supportive therapy but these findings are based on a few small studies where we graded the evidence as very low quality. Future research would benefit from larger trials that use supportive therapy as the main treatment arm rather than the comparator.